APLIKASI METODE RUN UNTUK PEMANTAUAN KEKERINGAN METEOROLOGIS DI KECAMATAN PUJUT KABUPATEN LOMBOK TENGAH - HUMAIRO SAIDAH; AGUSTONO SETIAWAN; MUH. BAGUS BUDIANTO (GANEC SWARA, 2024)
Drought is a disaster frequently experienced in Pujut District, Central Lombok Regency. Almost every year, this area suffers from prolonged drought. This study was conducted to understand the characteristics of the droughts that occur, using a widely recognized drought assessment method as an effort to mitigate drought disasters in this region. The drought assessment used in this study is the Run method. This method was chosen due to its simplicity and the fact that it only requires rainfall data for its analysis. The results of the calculations for the depth and duration of the drought period are then compared with past droughts in the region and the natural phenomena that influenced them. The analysis using the Run method shows that the most severe and longest drought occurred at Pujut District from July 1997 to May 1998 (11 months) with a deficit of 800 mm from the average normal rainfall, and from 2014 to 2015 with a deficit of 553.54 mm. Both extreme droughts in 1997 and 2015 occurred in various regions of Indonesia and were related to the strong El Niño phenomenon occurred at that time